The Effect of Problem Solving Model Towards Higher Order Thinking Skills and Students Learning Activities - Waliyyatu Azzahra; Heffi Alberida (Bioeducation Journal, 2020)
This study aims to determine the influence of the application of Problem Solving Model towards higher order thinking skills and learning activities of Class X students in SMAN 3 Bukittinggi. This type of research is an experimental study with a Random Design Only Posttest Design Group. The research subjects were 32 students of Class X MIPA 2 SMAN 3 Bukittinggi who were registered in the 2019/2020 school year. The research instrument for obtaining high order thinking skills data is an objective form of question sheet, while the learning activities data obtained through the observation sheet filled by observers. The results showed the average value obtained in the class applied the Problem Solving Model was 76.06. This value is higher when compared to the average value in the control class, which is 66.19. Learning activities of students with the application of the Problem Solving Model, namely for oral activity 73.44%, visual activity 93.76%, and writing activity 96.88%. This percentage is also higher than the control class which has a percentage of 42.19%, 84.38%, and 75%. Based on the results of the study, it can be conclude that the Problem Solving Model has a significant positive effect on the increase in high order thinking skills and learning activities of Class X students of SMAN 3 Bukittinggi. Keywords: Problem Soving, HOTS, Learning Activities